MENGEMBANGKAN PLURALISME HUKUM SEBAGAI PONDASI HUKUM MASA DEPAN INDONESIA - Arman, Zuhdi; Agus Riyanto (Universitas Muhammadiyah Bima, 2023)
The emergence of double law in social life is known as legal pluralism. Legal pluralism in Indonesia emerged and developed as a result of the country's historical factors, which included differences in ethnicity, language, culture, religion, and race. However, although pluralism has various etymological meanings, they all have one thing in common: recognizing the reality of all differences. The purpose of this research is to find out the concept of legal pluralism that is used to restore customary law in an effort to protect indigenous peoples' natural resources from appropriation authorized by the state. This study also uses a normative legal approach, which is a process to find a rule of law, legal principles, or legal doctrines to answer the legal issues at hand. Almost every state law that regulates natural resources now has rules regarding indigenous peoples. Pro-indigenous activists are still leading the movement to promote recognition of indigenous peoples at a practical level. Among other things, by collecting data on customary law and mapping customary territories in various locations. Because these two factors are the main prerequisites for recognizing the existence of indigenous peoples. This is considered as one of the solutions to the weakness of the state dispute settlement institution (court) which is deemed unable to provide substantive justice. This movement basically proposed that the people solve their own problems without the help of the courts.